Islam Kontemporer: Antara Otoritas Teks dan Dinamika Zaman - Faathir Janwar; Muhammad Naufal Marifat; Kurniati Kurniati (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
Contemporary Islamic law faces complex challenges in responding to rapid social change while maintaining fidelity to authoritative religious texts. This article examines the tension and interaction between textual authority (the Quran, Sunnah, ijma’, and qiyas) and the dynamics of modern socio-cultural, political, and technological developments. Using qualitative library research, this study analyzes classical and contemporary Islamic legal thought, including maqaṣid al-shariah, ijtihad, and contextual interpretation. The findings indicate that Islamic law possesses inherent flexibility through its methodological tools, enabling adaptation without undermining its normative foundations. However, challenges arise from rigid textualism, politicization of Islamic law, and epistemological gaps between tradition and modernity. This study concludes that a balanced approach integrating textual fidelity and contextual responsiveness is essential for the relevance of Islamic law in contemporary society.